Aplikasi Kamus Istilah Komputer Pada Perangkat Mobile Menggunakan fitur Voice, Abjad dan Kategori Berbasis Android - Farid Idham; Ona Maliki (JSAI (Journal Scientific and Applied Informatics), 2022)
The dictionary, the term computer widely circulated today, is still in the form of books. Many make it difficult for users because they have to search for the meaning and terms of the computer manually. The method used in this research using the Research and Development method, where the researcher conducts fact gathering that refers to the KBBI dictionary. It was then built using the android studio application as a medium to create an information system term computer dictionary.Â  With this Android-based dictionary, anyone and anywhere anyone can access it easily. For that, there is a need for a dictionary of terms, computers to facilitate the public in understanding the meaning of words and terms of computers in the form of mobile applications, especially android-based.